An Introduction to Maple V - Cornil, Jack-Michel (Springer Berlin Heidelberg, 2001)
This book covers the needs of scientists - be they mathematicians, physicists, chemists or engineers - in terms of symbolic computation, and allows them to locate quickly, via a detailed table of contents and index, the method they require for the precise problem they are adressing. It requires no prior experience of symbolic computation, nor specialized mathematical knowledge, and provides quick access to the practical use of symbolic computation software. The organization of the book in mutually independent chapters, each focusing on a specific topic, allows the user to select what is of interest without necessarily reading everything.